Religion, Power, and Culture: Islamization in the Mempawah Kingdom under Opu Daeng Manambon (1741-1761) - Patmawati; Zaenuddin Hudi Prasojo; Bob Andrian; Barriyati; Muhammed Sahrin Bin Haji Masri (UIN Sunan Kalijaga Yogyakarta, 2026)
This study examines the historical spread of Islam within the Mempawah Kingdom, focusing on the interplay between religion and culture during the reign of Opu Daeng Manambon (1741–1761). Specifically, it seeks to elucidate the processes of integrating religion and culture, the implementation of daʿwah strategies in the propagation of Islam, and the respective roles of the umarāʾ and ʿulamāʾ during this period. Employing qualitative research methods grounded in a historical approach, the study utilizes heuristic techniques, including criticism, synthesis, and historiography, applied to historical materials from West Kalimantan, with particular emphasis on the Mempawah Kingdom. The findings reveal that Islamization under Opu Daeng Manambon was not merely a peaceful cultural diffusion but rather a politically structured and culturally negotiated transformation. This process was shaped through interactions among royal authorities, networks of ʿulamāʾ, trade relations, and local socio-cultural dynamics. The study further demonstrates that Islamization developed through a hybrid daʿwah model that integrated political influence, cultural adaptation, and dialogical engagement, reflecting a collaborative power dynamic between rulers and ʿulamāʾ within a multicultural society. Ultimately, this study contributes to ongoing discussions on the processes of Islamization in Southeast Asia.